2020
DOI: 10.5812/compreped.94278
|View full text |Cite
|
Sign up to set email alerts
|

Serum Magnesium Levels in Neonatal Jaundice: Is There any Correlation Between Hypermagnesemia and Moderate to Severe Hyperbilirubinemia in Term Newborns?

Abstract: Background: Neonatal jaundice is a common major problem; on the other hand, it is suggested that there is a correlation between plasma magnesium concentrations and hyperbilirubinemia during the neonatal period.Objectives: The study aims to validate a previously reported risk index for predicting the magnesium level of plasma for moderate to severe hyperbilirubinemia in infant neonates. Methods: A cross-sectional correlation study was performed on 93 term newborns with indirect hyperbilirubinemia admitted in ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…(26) In addition, Mg levels were found to increase in case of toxicity caused by high bilirubin levels. (27) Thus, it can be said that the fact that AG did a total of 7 competitions (525 minutes), including one high-intensity competition (75 minutes) every day, (28,29) caused an increase in serum Mg values. (30) Already, our study findings and the data in the literature suggested that high Mg levels in field hockey athletes play a role in the maintenance of the necessary biochemical processes in removing toxic metals from the body and suppressing oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…(26) In addition, Mg levels were found to increase in case of toxicity caused by high bilirubin levels. (27) Thus, it can be said that the fact that AG did a total of 7 competitions (525 minutes), including one high-intensity competition (75 minutes) every day, (28,29) caused an increase in serum Mg values. (30) Already, our study findings and the data in the literature suggested that high Mg levels in field hockey athletes play a role in the maintenance of the necessary biochemical processes in removing toxic metals from the body and suppressing oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Paul et al, [7] didn't nd any signi cant in IVH incidence and mortality rate between infants born to mothers with preeclampsia as compared to infants born to mothers without preeclampsia. It may be partly due to magnesium sulfate treatment in mothers with preeclampsia, which acts as a neuroprotective agent in their neonates [7,15].…”
Section: Discussionmentioning
confidence: 99%
“…В Таблиці 1 наведена базова клінічна характеристика 58 передчасно народжених дітей з урахуванням оцінки стану після народження за шкалою Апгар залежно від клінічного перебігу. Окремі автори робили спробу пов'язати гіпомагніємію з гіпербілірубінемією, але не було виявлено ані позитивної, ані негативної значущої кореляції між рівнем магнію та білірубіну [8], а в нашому дослідженні ми не виявили жодних значущих кореляцій гіпомагніємії з маркерами ендотеліальної дисфункції (варіантами гена eNOS, рівнем оксиду азоту) та наявними клінічними симптомами і тяжкістю перебігу. Натомість нами була встановлена позитивна кореляція між рівнем оксиду азоту та ступенем дихальної недостатності.…”
Section: результати та їх обговоренняunclassified